Improving English Pronunciation of Adult ESL Learners through Reading Aloud Assessments - Siti Nurani; Amrina Rosyada (Bina Nusantara University, 2015)
Communication skill nowadays becomes a must that everyone should master. The agreement of such conceptual meaning in communication should meet the same perception among speakers. One of the tools to improve one’s communication skill is by learning pronunciation through Reading Aloud for misperception emerged from mispronunciation can be avoided. This research aims at improving English pronunciation through reading aloud in the form of short texts. The research was carried out in Statistics Data Center (BPS) by employing A Classroom Action Research with two cycles of assessments. There were 20 IT engineers of Networking Operation Center with various background of knowledge as an object of the research. The data was collected by observation, note taking, and test. Questionnaire is designed and administered to identify the participants’ core and frequency of English tasks and also to investigate participants’ previous experiences with English. Findings show that there is an improvement on participants’ pronunciation skill through Reading Aloud as it can be seen from the increase of a mean score on the second cycle with 77.75 that is considered as good predicate.